2022
DOI: 10.1108/ijpdlm-12-2021-0511
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain risk management strategies in normal and abnormal times: policymakers' role in reducing generic medicine shortages

Abstract: PurposeThis paper links supply chain risk management to medicine supply chains to explore the role of policymakers in employing supply chain risk management strategies (SCRMS) to reduce generic medicine shortages.Design/methodology/approachUsing secondary data supplemented with primary data, the authors map and compare seven countries' SCRMS for handling shortage risks in their paracetamol supply chains before and during the first two waves of the COVID-19 pandemic.FindingsConsistent with recent research, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Despite the daunting perception of formal theories and frameworks, mid-range theories (Stank et al ., 2017; Pellathy et al ., 2018; Russo et al ., 2021; Wowak et al ., 2022; Stank et al ., 2022), abductive theory elaboration approach (Kovács and Spens, 2005; DuHadway et al ., 2022; Ahlqvist et al ., 2023; Norrman and Prataviera, 2023; Russo et al ., 2023; Bals et al ., 2023; Sawyerr and Harrison, 2023) offer viable entry points for scholars who may otherwise be hesitant to engage in theorizing. Design science shapes and refines solutions, emphasizing pragmatic validity and long-term outcomes.…”
Section: Superficial/inappropriate Use Of Theorymentioning
confidence: 99%
“…Despite the daunting perception of formal theories and frameworks, mid-range theories (Stank et al ., 2017; Pellathy et al ., 2018; Russo et al ., 2021; Wowak et al ., 2022; Stank et al ., 2022), abductive theory elaboration approach (Kovács and Spens, 2005; DuHadway et al ., 2022; Ahlqvist et al ., 2023; Norrman and Prataviera, 2023; Russo et al ., 2023; Bals et al ., 2023; Sawyerr and Harrison, 2023) offer viable entry points for scholars who may otherwise be hesitant to engage in theorizing. Design science shapes and refines solutions, emphasizing pragmatic validity and long-term outcomes.…”
Section: Superficial/inappropriate Use Of Theorymentioning
confidence: 99%
“… 23 Ahlqvist et al identified the role of policymakers in applying supply chain risk management strategies (SCRMS) to mitigate generic medicine shortages in both normal and abnormal times and evaluated the strategies adopted by policymakers in managing shortage risks in the medicine supply chains of seven countries before and during the COVID-19 pandemic. 24 Different from their studies, our work focuses on blockchain adoption for generic drugs in medicine supply chains considering consumers’ risk-aversion and quality uncertainty of generic drugs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stockouts and shortages are challenges in retail and healthcare SCs, prompting strategies for inventory management and coordination [51][52][53]. Additional risk and product returns impact agricultural SCs, highlighting the importance of understanding factors contributing to returns and mitigation strategies [54].…”
Section: Sc Sectorsmentioning
confidence: 99%